Behavior of thermal spray coatings against hydrogen attack - Latorre, Guillermo; Vargas, Fabio; Uribe, Iván (CT&F - Ciencia, Tecnología y Futuro, 2003)
The behavior of nickel and chrome alloys applied as thermal spray coatings to be used as protection against embrittlement by hydrogen is studied. Coatings were applied on a carbon steel substrate, under conditions that allow obtain different crystalline structures and porosity levels, in order to determine the effect of these variables on the hydrogen permeation kinetics and as a protection means against embrittlement caused this element. In order to establish behaviors as barriers and protection, hydrogen permeation and corrosion tests under stress were carried out, supported by measurements of the potential’s drop in the substrate-coating system under simultaneous conditions of stress and a corrosive agent with H2S in solution. Findings show that alloy coatings with face centered cubic structure possess greater hydrogen solubility than coatings with body centered cubic structures and than carbon steel used as substrate. Additionally, porosity inherent to the formation of this type of coating reduces hydrogen diffusion through its structure. The analysis of these results allows selecting the coating with better performance as a protection means against embrittlement by hydrogen.